(untitled) (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2013)
This paper analyses the Spanish industry throughout the study of different subjects related to a) the structural characteristics of the Spanish factories, b) the manufacturing strategy deployment, c) the agile manufacturing development, and d) the stage of the production function in the firm. It uses data from a mail survey performedon a wide sample of firms, representative of the Spanish industry. The analyses show two particularities dominating the Spanish industry: concentration and dependency. Additionally, new trends in the strategic production management are observed.